Implementasi Keperawatan Latihan Rom Pasif Pada Pasien Stroke Non Hemoragik Dengan Gangguan Mobilitas Fisik - Mediarti, Devi; Syokumawena, Syokumawena; Rosyada, Tahirrou (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Non-hemorrhagic stroke occurs due to a blockage in the lumen of the blood vessels of the brain and has the highest prevalence in Indonesia. The problem that arises is decreased muscle strength. Passive ROM implementation can reduce physical mobility disorders. Method: Descriptive method in the form of a case study. Nursing Care Approach consisting of assessment, nursing diagnosis, planning, implementation, evaluation and nursing documentation. There were 2 subjects in this study, namely men and women with the same criteria, namely non-hemorrhagic stroke patients. This research was conducted at the Siti Fatimah Hospital in South Sumatra Province. Results: The results of mobilization support with non-pharmacological techniques in the form of Passive ROM exercises to increase muscle strength in non-hemorrhagic stroke patients were carried out for 3 consecutive days, range of motion increased and muscle weakness decreased. Patient 1, the muscle strength of the upper and lower extremities on the left previously scored 1 increased to a score of 2. Patient 2, the muscle strength of the upper and lower extremities on the right previously had a score of 2 to a score of 3. Conclusion: After Passive Range Of Motion is effective in the healing process of non-hemorrhagic stroke patients with impaired physical mobility, patient 1 and patient 2 increase muscle strength.